PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI SEGITIGA - Hamzah, M. Ali Imron; Alhusna, Elma; Ni’mah, Masrifatul; Budi Rahaju, Endah; Wahyu, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low mastery of geometric concepts regarding the congruence of two triangles experienced by students in junior high schools makes teachers have to think of ways to improve the learning process. This research aims to determine the effect of using Augmented Reality-based learning media on the learning outcomes of class VIII-K students at SMP Negeri 8 Kediri. This research uses a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design type. Determining the sample in this study used probability sampling techniques. The sample in this research was 34 students in class VIII-K of SMP Negeri 8 Kediri. The data collection method uses pretest-posttest, while data analysis uses t-test. The research results showed that the average coefficient of student scores during the pretest-posttest was , sig. (2-tailed) is smaller than , namely and the Tcount>Ttable value, namely . So that it can be said that there is an influence of the use of Augmented Reality-based learning media on the mathematics learning outcomes of triangle material in class VIII-K students at SMP Negeri 8 Kediri.